Perlindungan Hukum Terhadap Dokter Dalam Melakukan Praktik Kedokteran Terkait Dengan Dugaan Pelanggaran Disiplin Yang Berdampak Terhadap Malpraktik - David Estrada (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
Malpractice can be interpreted as an act of negligence, error or a doctor's lack of ability to treat a patient so that it causes a bad outcome for the patient. Several malpractice cases that ended in decisions that did not blame the doctor and sanctions that were considered light were one of the things that made some people think that this law was not at all in favor of malpractice cases. Several doctors questioned how legal certainty would be for them if the Indonesian Medical Discipline Honorary Council (MKDKI) had decided that no disciplinary violations had been committed but the district court said otherwise. So, according to the author, it is necessary to carry out an analysis regarding the severity of the sanctions imposed by the Indonesian Medical Discipline Honorary Council and what the legal protection is for doctors who are suspected of practicing medicine related to disciplinary violations. This research uses the juridical-normative method, namely research conducted by examining the laws and regulations that apply or are applied to a particular legal issue. Indonesian Medical Discipline Honorary Council has the authority to handle violations of doctor's discipline. If there is a doctor's action that is classified as malpractice, Indonesian Medical Discipline Honorary Council can only be guided by a doctor's disciplinary violation. Disciplinary sanctions for doctors by the MKDKI include giving a written warning, recommending revocation of the STR or SIP and the obligation to take part in education or training at a medical/dental educational institution. The Indonesian Medical Discipline Honorary Council decision does not preclude the possibility for the doctor concerned to be examined, processed or sued criminally or civilly, because the Indonesian Medical Discipline Honorary Council decision has nothing to do with the application of law and criminal or civil legal sanctions and is basically a complaint, examination, up to the the Indonesian Medical Discipline Honorary Council decision or a public report. against doctors suspected of committing ethical violations is only limited to the ethics of the medical profession itself, which cannot be confused with the investigation process at the police, the prosecution process at the Prosecutor's Office until the court, or the lawsuit process at court.